The Role of Abstract Painting in the Educational Development of Aesthetic Criticism - Fahmi Hussein, Mayyadha (Opción, 2019)
The purpose of the study is to flourish the ground to new techniques to be used by interior design students in order to widen the criticism and the analysis of art in the educational curriculums of interior design via the experimental method. As a result, the result of the products in the interpretation phase was greater than the result of the judgment by studio practice. In conclusion, it’s a very normal reaction from university students to add their own judgment and personal views to interpret a work of art.